Predictors of children's physical activity in the early years foundation stage. (June 2022) - Woodfield, Lorayne; Tatton, Allison; Myers, Tony; Powell, Emma
The physical activity (PA) of young children is critical to their future activity, health and development, however, little is known about how the organisation of early years foundation stage (EYFS) settings impacts upon children's PA. This study aimed to measure the PA of children in Nursery and Reception classes and to explore their PA according to learning context. Participants were 191 EYFS children (boys = 89; girls 102; Mean age M  = 4.6, SD = 0.7 years) from six schools in the West Midlands, UK. Systematic observation was used to record children's PA, learning context, adult interaction and location throughout the EYFS day. A total of 8740 observed intervals occurred. Children spent two thirds of their time being stationary (65.8% and 69.8% for Nursery and Reception respectively). Results of beta regression revealed the strongest predictors of vigorous PA (VPA) to be the learning contexts of 'role play', 'physical', 'construction' and being 'outside'. Adult interaction had a negative association with moderate to vigorous PA (MVPA), and girls have 16.36% lower odds of engaging in VPA and 19.4% higher odds of engaging in stationary behaviour than boys. In order to support children's learning and development, teaching strategies and the organisation of the EYFS environment should be adapted to increase children's, especially girls', active learning and to reduce sedentary time.